Implementasi Rencana Kerja Pemerintah (RKP) Nagari dalam Meningkatkan Pembangunan dan Kesejahteraan Masyarakat: (Studi pada RKP Nagari Koto Baru Tahun 2026) - Witra Maison; Wahyuni Lili; Afchellya Anugrah Putri; Zahara Putri Amril; Jabil Rahmatullah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the implementation of the 2026 Nagari Government Work Plan (RKP) of Koto Baru Nagari in supporting development and improving community welfare. The RKP is an annual planning document that serves as a guideline for the nagari government in implementing development programs based on community needs and the objectives outlined in the Nagari Medium-Term Development Plan (RPJM). This study employed a descriptive qualitative approach using field research methods. Data were collected through interviews and documentation. The findings indicate that the preparation of the 2026 RKP was conducted through participatory deliberation involving the nagari government, local institutions, and community representatives. The total budget allocated for the 2026 RKP is approximately Rp6.9 billion, sourced from Village Funds, Village Fund Allocations, and Nagari Original Revenue. Priority programs include the construction of a health service facility (Poskesri), farm road development, food security programs, community incentives, and direct cash assistance. The main challenge in implementation is limited funding resources. Evaluation is carried out through sector-based monitoring of program realization and budget utilization. The study concludes that the RKP plays an important role in creating participatory, transparent, and accountable development while improving community welfare.